RAMONA—Rangeland Monitoring for Africa Using Earth Observation: Continental Demonstrator - Griffiths, Patrick (European Space Agency, 2025)
A presentation on RAMONA, the Rangeland Monitoring for Africa as part of an experience sharing webinar with the Agricultural Transformation Institute, who are developing a national rangeland monitoring system for Ethiopia.